Critical Success Factors for Private and Public-Private Partnership Investments in Renewable Energy Development in Kenya - Achieng, Jectone (2019)
Drivers or Critical Success Factors (CSFs) for IPPs and PPPs in renewable energy have been well researched and documented in many developed countries and significant literature exist. In Africa, studies on drivers of renewable energy development have focused on North Africa and South Africa. This study sought to identify the drivers of renewable energy in a developing or middle- income country like Kenya. Further, while previous studies have adopted various methodologies, this study employed a three-stage survey approach focusing on the context of the renewable energy investments as reflected by the prevailing conditions in the macro-business environment, the structure of the electricity sector and project profiles or characteristics as determinants. The study relied on the views of project developers (including consultants and contractors), Development Financial Institutions; Commercial Financial Institutions, Government and Government Agencies, various professional groups and academic researchers, who were the main target groups for the study. On the macro-business environment level, two key macro-level determinants of renewable energy development in Kenya were identified as political goodwill and quality of the country’s development plans. Political support was viewed as a key ingredient for any investment in the country as it serves to reduce political risk and secures investors’ interest while the country’s development plans provide a benchmark against which developers based their investment decisions. Regarding the influence of the structure of the electricity sector, independence of the regulator was ranked as the leading driving factor for renewable energy investments in Kenya followed by the Government support to the off-taker. Project profiles determinants for renewable energy development in Kenya had interesting results. Environmental and social issues was identified as major project factor influencing private players’ participation in the sector. Stakeholder management in Kenya was rated as excellent and supports projects success in Kenya. However, quality of environmental laws and standard, local population support and ease of obtaining access and way-leaves remains of concern for renewable energy developers. Other project profiles considerations identified as driving renewable energy development in Kenya included participation of Development and Financial Institutions and Multi-Lateral Institutions in the Kenya Energy Market, growing demand for electricity, adequacy of tariffs and proven technology and availability of local capacity.